A double-blind, randomized clinical study to determine the efficacy of benzocaine 10% on histamine-induced pruritus and UVB-light induced slight sunburn pain. (August 2015) - Bauer, Martin; Schwameis, Richard; Scherzer, Thomas; Lang-Zwosta, Isabelle; Nishino, Kanako; Zeitlinger, Markus
Abstract Introduction: This study aims to explore the efficacy of the topical application of 10% benzocaine for treating pruritus and pain as compared to vehicle ointment. Methods: Twenty male subjects were treated in a randomized double-blind fashion with the investigational medicinal product (IMPD) and vehicle. Immediately after the injection of 100 µg histamine on both arms, subjects received topical treatment and pruritus was subsequently assessed with visual analogue scale (VASpruritus) and Eppendorfer questionnaire. Ultraviolet B radiation (UVB) was administered on the back to induce slight sunburn. Twelve hours after UVB application again the IMPD was applied on the right or left upper back and vehicle on the other side and pain related to sunburn was measured with VASpain and pressure algometry. Results: A trend towards better reduction of pruritus was shown for benzocaine in VASpruritus. For the VASpain significant differences in group comparison (p = 0.02) were observed. Algometer measurements showed onset of pain reduction in the verum group after 20 min whereas in the vehicle-treated area pain relief occurred only after 60 min after application. Conclusions: The topically administered ointment containing 10% benzocaine was found superior over vehicle for treating pain, but not pruritus.